Cooking Pattern and Eating Behaviors in Association with Socioeconomic Status among Iranian Households: The NUTRI-KAP Survey - Forouzan SALEHI; Zahra ABDOLLAHI; Maryam SANAEI; Mostafa QORBANI; Zeinab AHADI; Gita SHAFIEE; Zeinab TIZNOBEYK; Bahar AZEMATI; Ramin HESHMAT (Tehran University of Medical Sciences, 2015)
Background: Disparities in health may relate to differences in nutrition. Among dietary determinants, Socioeconomic Status (SES) plays an important role. Therefore, this study was aimed to investigate the association between SES and cooking pattern and consumed food among rural and urban Iranian households.     Methods: Overall, 14,136 households were selected through single-stage cluster sampling methods from urban and rural regions of 31 provinces of Iran in 2011-2012. Demographic, SES, cooking pattern and consumed food data were obtained through valid structured questionnaires by interviewing between trained interviewers with qualified people in households. Data were analyzed using STATA software ver. 11.0 (STATA Corp, College Station, Tex.) Results: In households with weak SES background, 70.4% of households cooked separately for any meal. The healthy cooking method for red meat and chicken, fish, celery, vegetables stew, onion and green bean was significantly higher in good SES ( P<0.001). Households with good SES had higher intake low fat dairy, liquid oil and iodized salt (P<0.001) compared with families with weak SES. Most consumed bread in three groups was Lavash (Local name).  Conclusion: Pattern of cooking and the type of consumed foods among different SES group and their relationship with each other. So based on this information will be facilitated for interventions and training for better nutrition pattern in society.     Keywords: Socioeconomic Status, KAP, Cooking pattern, Consumed food